Brazilian regions in the global value chain: trade and the environment - Imori, Denise (2015)
This dissertation analyzes economic and environmental aspects related to Brazilian states\' participation in global value chains. It is composed by three essays. In the first essay, a novel methodological framework is proposed for estimating a country-state input-output table, combining a world table and an interregional table. In the proposed framework, input coefficients from both datasets are employed (rather than the intermediate flows). The empirical application combines a world input-output table covering 40 countries (and the rest of the world as a 41st country) with an interregional input-output table covering all Brazilian states, for the year 2008. The essay proceeds with the analysis of the Brazilian states\' trade in value added, with special focus on foreign trade. It is observed that the importance of production sharing for participating in the global value chains varies widely across states. International trade in value added is highly concentrated in the more developed Southeast and South regions. These regions are also majorly responsible for linking other states\' production to final consumption abroad, that is, they act as major links connecting and extending Brazilian production networks to the global value chains. The underlying geographical structure of global value chains is the object of study in the second essay. Firstly, background perspectives are presented on how the fragmentation of production processes has lead to the reorganization of economic activities around the globe and within countries. Then, the hierarchical feedback loop methodology is applied to the previously estimated country-state input-output table. A great degree of production sharing among Brazilian states is observed. The results indicate that fragmentation within great regions is a major phenomenon for the Southeast and (secondary to the links with São Paulo) the South regions. For states elsewhere in the country, supply chain connections with the more developed states in Brazil overshadows production sharing with neighbouring states. In this way, the geography of production within Brazil seems to remain quite similar over the years. At global level, a spatial structure is observed where the flows linking major economies across trade blocks are dominant; the results support that production fragmentation is a truly global phenomenon, not being merely circumscribed to trade blocks. Finally, the third essay turns to the environmental aspects of the integration in global value chains. More specifically, to the relationship between trade and CO2 emissions. The interrelationships between states in environmental matters are relevant in large and heterogeneous countries such as Brazil, where the regional distributive aspect of mitigation policies is a concern. The analysis traces the CO2 emissions from fossil fuel combustion embodied in Brazilian states\' trade both within the country and internationally. The previously estimated country-state IO table is applied together with a novel database reflecting CO2 emissions from fossil fuel combustion by state and productive industry. A central finding is that not only were 28% of global emissions (from fossil fuels) embodied in international trade, but 36% of territorial emissions (from fossil fuels) in Brazil were traded between states in 2008. Thus, international and interregional trade play a major role in emissions reduction and should be given due consideration in the climate change policy framework. The current regional mitigation initiatives in Brazil, which are limited to a few states and refer only to the emissions generated within states\' territorial boundaries, ignore an important share of national emissions.